(untitled) (International Journal of Engineering and Computer Science, 2015)
today lot of valuable data is generated using many computers based application and stored back to the company database. But unfortunately, the threat to the same data is also increasing rapidly. So, development of a proper Intrusion Detection System which provides a right alarm is a hot topic today. A set of rules are used by Signature based Network Intrusion Detection Systems (NIDS) to detect hostile traffic in network segments or packets, which are so important in detecting malicious and anomalous behavior over the network like known attacks that hackers look for new techniques to go unseen.Theproblem of network intrusion detection is not just to identify theattacks connections, but also to know what type of an attack theconnection belongs to. The paper aims to build an innovative functional framework to NIDS. This framework can be used to audit NIDS.This framework shows that a proof of concept showing how to categorize the attacks.